2001
DOI: 10.1006/dbio.2001.0194
|View full text |Cite
|
Sign up to set email alerts
|

FGF Signaling in Chick Lens Development

Abstract: The prevailing concept has been that an FGF induces epithelial-to-fiber differentiation in the mammalian lens, whereas chick lens cells are unresponsive to FGF and are instead induced to differentiate by IGF/insulin-type factors. We show here that when treated for periods in excess of those used in previous investigations (>5 h), purified recombinant FGFs stimulate proliferation of primary cultures of embryonic chick lens epithelial cells and (at higher concentrations) expression of the fiber differentiation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
116
0
1

Year Published

2003
2003
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(122 citation statements)
references
References 72 publications
5
116
0
1
Order By: Relevance
“…4 shows that retinal cell differentiation is disrupted by these inhibitors and supports our hypothesis that the MAP kinase pathway is critical for this process. Interestingly, MEK 1͞2 inhibitor injections at earlier time points severely disrupted lens differentiation consistent with previous in vitro studies investigating the role of MAP kinase signaling on lens differentiation (32,33).…”
Section: Resultssupporting
confidence: 87%
“…4 shows that retinal cell differentiation is disrupted by these inhibitors and supports our hypothesis that the MAP kinase pathway is critical for this process. Interestingly, MEK 1͞2 inhibitor injections at earlier time points severely disrupted lens differentiation consistent with previous in vitro studies investigating the role of MAP kinase signaling on lens differentiation (32,33).…”
Section: Resultssupporting
confidence: 87%
“…Previous studies showed that FGF-1 and FGF-2 promote lens cell proliferation and lens fiber differentiation in explant cultures (4,31). Whether these two effects are achieved via identical or distinct mechanisms remains to be clarified.…”
Section: Discussionmentioning
confidence: 96%
“…7). It is important to note that ERK1/2 kinases are also downstream of insulin-mediated signaling in lens (Le and Musil, 2001). The PI3K branch of FGF-signaling associates with the complex via Gab1 that is recognized by the p85 regulatory subunit of phosphatidylinositol-3-kinase (PI3K).…”
Section: Fgf Signaling In Lens Differentiation-a Schematic Diagram Ofmentioning
confidence: 99%